Perbandingan Perkembangan Prinsip Hukum Ekonomi Syariah di Indonesia, Malaysia, dan Brunei Darussalam - Zulkifli (CV.Karoteh Utama, 2022)
This study aims to examine the development of sharia economy law in three selected countries as seen from the progress of Islamic banking in the Southeast Asian Region. The objects of this study are Indonesia, Malaysia and Brunei Darussalam. The method used is descriptive analytical with normative juridical approach and literature review. The results showed differences in the development of sharia economic law in the three countries studied but not significantly. The practice of resolving sharia economic disputes in Indonesia by litigation can be resolved into 2 alternatives, namely by simple (MA Regulation Number 14 of 2016) and ordinary (MA Regulation Number 2 of 2015). While Islamic banking in Malaysia has sharia economic laws, namely the Islamic Banking Act (IBA) and the Bank and Financial Institutions Act (BAFIA). While in Brunei Darussalam refers to the principles of anti-usury, Ijarah, Musyarakah Musawwamah and certificates and other relevant sharia economic regulations that are manifested from various services and banking products.